Variation of Cognitive Function During a Short Stay at Hypobaric Hypoxia Chamber (Altitude: 3842 M) - De Bels, D.; Pierrakos, C.; Bruneteau, A.; Reul, F.; Crevecoeur, Q.; Marrone, N.; Vissenaeken, D.; Borgers, G.; Balestra, C.; Honoré, P. M.; Theunissen, S. (Frontiers in Physiology, 2019)
Objective: To observe the effects of a fast acute ascent to high altitude on the brain cognitive function, and on the vascular systemic function to understand the compensation mechanisms on cardiac and cerebral parameters. Methods: 17 male subjects participated in the study. We measured Saturation, Heart Rate, Velocity Time Integral (VTI), Systemic Vascular Resistance (SVR), Cardiac Output, Blood Pressure, Psychology Experiment Building (PEBL), Critical Flicker Fusion Frequency (CFFF), Cerebral Blood Flow index (CBFi), mean cerebral artery Systolic and diastolic velocities, Cerebral Pulsatility index (CPi), all measured at sea level, at 3842m and 1hour after return to sea level. Results: Under acute exposure to hypobaric hypoxic conditions, significant decrease in saturation, CBFi, CFFF, Blood Pressure (p<0,05) were observed accompanied by a significant increase in Heart Rate. There was no significant change in PEBL, Systolic and Diastolic velocities or CPi, Except for Blood Pressure, all the parameters returned to their basal values. Conclusion: Hypoxia results in decreased oxygen saturation, increased heart rate and cardiac output. The decrease in CBFi does not explain the maintenance of cognitive performance after acute exposure to hypobaric hypoxia and requires further investigation. CFFF decreases at high altitude.